Modelling dynamic properties in the layered model for XML using Xsemantic nets - Rajugan, R.; Chang, Elizabeth; Feng, L.; Dillon, Tharam S. (Springer-Verlag, 2006)
Object-Oriented (OO) conceptual modelling offers the power in describing and modelling real-word data semantics and their inter-relationships in a form that is precise and comprehensible to users [1]. Conversely, XML [2] is becoming the dominant standard for storing, describing and interchanging data among various Enterprises Information Systems and databases. With the increased reliance on such self-describing, schema-based, semi-structured data language/(s), there exists a requirement to model, design, and manipulate XML data and the associated semantics at a higher level of abstraction than at the instance level.However, existing Object-Oriented conceptual modelling languages provide insufficient modelling constructs for utilizing XML schema like data descriptions and constraints, while most semi-structured schema languages lack the ability to provide higher levels of abstraction (such as conceptual models) that are easily understood by humans. To this end, it is interesting to investigate conceptual and schema formalisms as a means of providing higher level semantics in the context of XML-related data engineering. In this paper, we use XML view as a case in point and proposed to model engineering. In this paper, we use XML views as a case in point and propose to model dynamic properties of a layered XML view model [3] using eXtensible Semantic (XSemantic) nets.In data molding, we can group the existing view models into four categories, namely [3]; (a) classical (or relational) views, (b) Object-Oriented (OO) views, (c) semi-structured (namely XML) view models [4-6, 3] and (d) view models for Semantic Web. Here, we focus only on view models for XML